T cell Dissimilarities in B Cell Activating Factor–Deficient Versus B Cell Activating Factor Receptor 3–Deficient Systemic Lupus Erythematosus‐Prone NZM 2328 Mice as Contributors to Their Divergent Clinical Outcomes - William Stohl; Ying Wu; Malka Stohl (ACR Open Rheumatology)
Objective We assessed the contributions of B cell and T cell subsets to the disparate clinical outcomes in NZM.Baff−/− and NZM.Br3−/− mice. Methods We assessed in NZM wild‐type, NZM.Baff−/−, and NZM.Br3−/− mice numbers and percentages of B cells and subsets, T cells and subsets, and in vivo proliferation and survival of forkhead box P3 (Foxp3)+ cells by fluorescence‐activated cell sorting. Relationships between percentages of Foxp3+ cells and numbers of CD19+ and CD4+ cells were assessed by linear regressions. Results In each age and sex cohort, percentages and numbers of CD19+ cells were similar in NZM.Baff−/− and NZM.Br3−/− mice. Percentages of CD3+ and CD4+ cells were greater in NZM.Br3−/− than in NZM.Baff−/− mice, with the CD4 to CD3 cell ratios being greater in NZM.Br3−/− than in NZM.Baff−/− mice and percentages of Foxp3+ cells in NZM.Br3−/− mice being lower than in NZM.Baff−/− mice. Percentages of Foxp3+ cells correlated positively with CD19+ cells in NZM.Baff−/− mice but negatively in NZM.Br3−/− mice. In vivo proliferation and survival of Foxp3+ cells were lower in NZM.Baff−/− mice than in NZM.Br3−/− mice. Conclusion Differences between NZM.Baff−/− and NZM.Br3−/− mice in Foxp3+ cells and their relationships with CD19+ cells may have more to do with their divergent clinical outcomes than do differences in numbers of B cells. These unexpected findings suggest that B cell activating factor (BAFF)–B cell maturation antigen (BCMA) or BAFF–Transmembrane activator and calcium‐modulator and cyclophilin ligand interactor (TACI) interactions may help drive development of clinical systemic lupus erythematosus (SLE) even under conditions of considerable B cell depletion. Insufficient blocking of BAFF–BCMA and BAFF–TACI interactions may lie at the heart of incomplete clinical response to BAFF‐targeting agents in human SLE.